A high-resolution mill pond record from eastern Virginia (USA) reveals the impact of past landscape changes and regional pollution history. (March 2019) - Balascio, Nicholas L.; Kaste, James M.; Meyer, Meredith G.; Renshaw, Madison; Smith, Kassandra; Chambers, Randolph M.
Abstract: Mill ponds appeared throughout the eastern United States following European settlement. Sedimentation in these systems records centuries of past landscape change. To date, mill ponds on the Atlantic Coastal Plain have received little attention, yet this region had the earliest colonial settlements. Mill ponds here also have potential to record geomorphic change and pollution histories at high-resolution because of easily erodible underlying unconsolidated sediments. This paper presents a c. 300-year record of sedimentation in Lake Matoaka, a former mill pond in Williamsburg, Virginia. We used lead (Pb) and cesium (Cs) isotopes ( 210 Pb, 137 Cs), Pb concentrations, stable Pb isotopes ( 206 Pb/ 207 Pb), and chronostratigraphic horizons to develop a chronology, which shows remarkably high sedimentation rates, ∼0.5 cm/yr. Sedimentological data including the analysis of organic matter, grain size, and elemental compositions, revealed past conditions within the lake and its watershed. These data are linked to the operation of the mill c. CE 1700–1910, changes in the dam structure, and other historic developments of the region. Tracing pollution history with 206 Pb/ 207 Pb showed mid-1800s atmospheric deposition from smelting of Upper Mississippi Valley district Pb ores, and a sharp maxima in total Pb of 134 μg/g in the 1970s from the peak use of leaded gasoline in North America. Mass accumulation rates climbed from c. 0.08 to 0.28 g/cm/yr during the 18th and 19th centuries from deforestation and agriculture, which is somewhat lower than sediment yields documented in other regions. We suggest that stream channel storage may buffer pond sedimentation within low gradient, coastal plain landscapes. This study contributes to the understanding of sedimentation in mill ponds for reconstructing historic landscape changes and regional pollution history.